A multicultural annotative bibliography of voice and voice disorders - Dejarnette, Glenda (Howard Journal of Communications, 1992)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-333-150-134-195 tex.type: [object Object]
Keywords: African american voice; Asian american voice; Hispanic voice; Multicultural voice; Multicultural voice disorders; Native american voice; dept.cmd

Computer‐assisted tracking simulation (CATS) - Dempsey, James J.; Levitt, Harry; Josephson, Judith; Porrazzo, Josephine (The Journal of the Acoustical Society of America, 1992)
The tracking technique involves a sender reading consecutive segments from a story and a receiver attempting to repeat each segment verbatim. The reliability and validity of the tracking procedure have been criticized based upon uncontrolled variables such as sender, receiver, and text characteristics. To address these problems, a computer-assisted interactive tracking simulation (CATS) system has been developed in which story segments are presented to the receiver via a video laser disc system and repair strategies are implemented through a computer program.
5 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1992JG99200008 tex.unique-id: [object Object]
Keywords: dept.cmd